Existing Screening Methods for Oral Cancer are Generally Acceptable to Patients in Non-dental Settings - Dodd, Virginia J. (The journal of evidence-based dental practice, 2015)
A systematic review of patient acceptance of screening for oral cancer outside of dental care settings. Paudyal P, Flohr FD, Llewellyn CD. Oral Oncol 2014 50(10):956–62. Virginia J. Dodd, PhD, MPH, RDH To determine the acceptability of screening for oral cancer outside of dental settings Information not available Systematic review Level 2: Limited quality, patient-oriented evidence Grade B: Inconsistent or limited-quality patient-oriented evidence